Is Technology for the Anthropocene an Impossibility? A Conversation about the Myko Project - Mark Antaki; Richard Janda (Law Text Culture, 2018)
We, the two interlocutors in this discussion, Mark Antaki and Richard Janda, have for the past number of years had periodic exchanges about the theoretical underpinnings and possible critique of a project that Janda has been leading, which seeks to signal to individuals the impacts of their choices upon collective environmental, health and social goods and to orient these individuals to make better choices. Antaki has sought to probe a number of paradoxes and challenges for legal normativity involved in using new forms of technology to address the accumulating and devastating externalities produced by our use of technology. A mutual fascination with the project and its critique led us to conclude that the discussion might have some broader saliency. This dialogue allowed us to share our preoccupations concerning the pervasive quality of technology in our lives and to explore how our efforts to redress the dominion of technology over nature might cede to the temptation to call upon new forms of technology in aid. Is this temptation to be resisted?